the Impact of religiosity, self awareness and trust on muzakki's interest to pay zakat in BAZNAS Langsa - Mustafa, Fakhrizal; Mustika Noor Mifrahi; Cici Pratiwi (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2022)
Abstract Objectives - This study aims to determine the factors that influence Muzakki's interest in paying zakat in Baznas Langkat Regency either partially or simultaneously. Methods - This study uses field research by conducting a survey of 95 people with a cluster random sampling approach. A regression test was conducted to determine the effect of religiosity, self-awareness and trust on muzakki's interest in paying zakat. Results - The results showed that the influence of religiosity and awareness partially had a significant positive effect on Muzakki's interest in paying zakat in Baznas, Langkat Regency. The effect of self-awareness on Muzakki's interest in paying zakat shows self-awareness. Meanwhile, trust shows an insignificant number, which means it does not affect interest in paying zakat in a positive direction. Limitations – This study has limitations in terms of the number of respondents. In addition, the research subjects are people who consistently pay professional zakat and do not include people who are reluctant to pay professional zakat. Implications – As a practical implication, the results can be used as a reference by the government, especially zakat institutions, in encouraging marketing strategies. To improve zakat payment in Baznas, they should consider the community's behaviour in paying zakat.